Heavy metal accumulation of medicinal plants growing on the territory adjacent to airfields - Довгопола, К. А. (Problems of Environmental Biotechnology, 2012)
The content of heavy metals was analyzed in soils and medicinal plants which were collected in the territory, adjacent to airfield "Zhulyany" in Kiev region, airfield in Nizhyn, Chernihiv region and in Phytopreparation.